Retro umbilical abscess mimicking infected urachal cyst: A rare presentation from migratory fish bone ingestion - Muhamad Hud Muhamad Zin; Theevashini Krishnasamy; Nik Ritza Kosai (Gazi Universitesi, 2021)
Foreign body ingestion, especially food bolus like a fishbone, is prevalent in the adult population, usually ingested accidentally with only a small percentage developing a complication. Once complications arises, it will have a wide variety of clinical manifestations. We present a case of a patient with an abdominal wall abscess resulting from migrating ingested fishbone that was treated with antibiotic therapy, drainage of the abscess, and removal of the foreign body.A 58-year-old gentleman presented to our hospital with chronic abdominal pain complaint from the right iliac fossa migrating to the umbilical region. His physical examination revealed swelling, redness, and tenderness over the umbilical region. Computed tomography showed a hypodense rim enhancing collection noted at the umbilical region with extension into the anterior peritoneal cavity with a thin linear dense structure within the collection measuring 4cm in length, likely representing a foreign body. He received antibiotic therapy and subsequently underwent abscess drainage and removal of a foreign body. He had an uneventful postoperative course, and follow up showed no recurrent. An abdominal wall abscess can arise from a complication of migratory fishbone ingestion. Unexplained abdominal wall abscess in an otherwise healthy individual should also raise suspicions of foreign body causing bowel perforation, and treatment should be tailored to the patient's presentation.